Measurements of water molecule density by tunable diode laser absorption spectroscopy in dielectric barrier discharges with gas–water interface. (5th December 2017) - Tachibana, Kunihide; Nakamura, Toshihiro; Kawasaki, Mitsuo; Morita, Tatsuo; Umekawa, Toyofumi; Kawasaki, Masahiro
Abstract: We measured water molecule (H2 O) density by tunable diode-laser absorption spectroscopy (TDLAS) for applications in dielectric barrier discharges (DBDs) with a gas–water interface. First, the effects of water temperature and presence of gas flow were tested using a Petri dish filled with water and a gas injection nozzle. Second, the TDLAS system was applied to the measurements of H2 O density in two types of DBDs; one was a normal (non-inverted) type with a dielectric-covered electrode above a water-filled counter electrode and the other was an inverted type with a water-suspending mesh electrode above a dielectric-covered counter electrode. The H2 O density in the normal DBD was close to the density estimated from the saturated vapor pressure, whereas the density in the inverted DBD was about half of that in the former type. The difference is attributed to the upward gas flow in the latter type, that pushes the water molecules up towards the gas–water interface.